Perencanaan Gedung Student Center UNISNU Jepara 5 Lantai Menggunakan Metode Sistem Rangka Pemikul Momen Khusus - Arba 'Alma, Brasyelia; Hidayati, Nor; Adi Saputro, Yayan (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2024)
Student center building is one of the facilities needed with the increase in the number of students at UNISNU Jepara which aims to support the needs of student learning activities on campus. Planning and calculation of the structure using SNI 2847-2019. The calculation of earthquake loads uses SNI 1726-2019 and the calculation of building loads uses SNI 1727-2019 and PPPIUG 1987. As for the structural modeling, it uses the help of SAP2000 software. The results of the structural planning include a 120 mm thick flat roof with reinforcement in the X direction of 10-200 and the Y direction of 10-250. Floor slabs are 120 mm thick with reinforcement in the X direction of 10-200 and the Y direction of 10-250. B1 25/50 with pedestal bending reinforcement 7D19 and rebar 10-150 and field bending reinforcement 4D19 and rebar 10-200. B2 25/50 with pedestal bending reinforcement 4D19 and rebar 10-150 and field bending reinforcement 3D19 and rebar 10-200. BA 20/40 with pedestal bending reinforcement 5D19 and rebar 10-100 and field bending reinforcement 2D19 and rebar 10-150. K1 50/50 with main reinforcement 8D19 and rebar 10-150. K1 50/50 with main reinforcement 6D19 and rebar 10-150.